European intellectual property institutions and Chinese foreign direct investment - Alexiou, Constantinos; Vogiazas, Sofoklis (Emerald, 2020)
Purpose We investigate the impact of the strength of intellectual property (IP) institutions on Chinese outward foreign direct investment (OFDI). Design/methodology/approach We use two different measures of IP on a sample of 21 European countries in the period 2003–2015. Panel quantile methodology is applied to assess the relationship at several points of the conditional distribution of OFDI. Findings We provide novel and robust evidence revealing a highly negative relationship between OFDI and the strength of IP institutions in Europe. This relationship which is more pronounced in the median and upper-quantiles, bolsters the conventional theoretical expectation that high institutional distance between home and host countries is inversely related to OFDI. Equally important is the preliminary evidence of the non-linear impact of IP at the median and upper-quantiles as well as the impact of other controlling variables such as GDP, population, trade openness and unit labour costs on Chinese OFDI. Originality/value The ensuing theoretical implications are of great significance for future studies on the institutional distance and drivers of OFDI by emerging economies as well as for European policymakers in so far as the strengthening of IP institutions constitutes a gravitational point for inward investment flows from China.
Keywords: China; Europe; Outward FDI; Intellectual property; Institutional environments; International property rights index